Digital education in the social investment model of Gross Domestic Product growth in the context of Industry 4.0 - Yankovskaya, Veronika V.; Suglobov, Aleksandr E.; Bykovskaya, Natalya V.; Mustafin, Timur A. (Frontiers in Education, 2023)
The motivation for this research was the desire to disclose the potential for human potential development that is created by Industry 4.0. The goal of this paper is to study the modern international experience and prospects for implementing the social investment model of economic growth under the conditions of Industry 4.0 with the help of the development of digital education. The method of regression analysis is used to model the econometric dependence of human development on digital education in 2019–2021. The paper’s contribution to the literature consists in the development of scientific provisions of the concept of the social investment model of economic growth through reconsidering the approach to human potential development with the help of education under the conditions of Industry 4.0. Unlike the existing approach, which implies the foundation on traditional (pre-digital) education, this paper offers a new approach to human potential development under the conditions of Industry 4.0, which is based on digital education. The advantage of the authors’ approach is its allowing for the fullest use of new opportunities that open under the conditions of Industry 4.0. The main conclusion of this research is that under the conditions of Industry 4.0, the social investment model of economic growth should be based on digital education. The theoretical significance of the results obtained lies in their allowing reconsidering the role of education in the implementation of the social investment model of economic growth under the conditions of Industry 4.0. It is proved that this role is performed most successfully with the help of digital education. The practical significance of the conclusions is due to the fact that implementation of the authors’ recommendations will allow balancing the level of human development in the countries of distinguished categories: countries with the highest Gross Domestic Product (GDP) growth rate; countries with the highest level of human development; countries with the most developed digital education. The social significance of the paper consists in its support for the practical implementation of SDG 4, SDG 8, and SDG 10.